Evaluation of the community impact of an educational intervention on sexually transmitted diseases directed at primary health care workers in the District of Matale. - Pathirana, G.C (My University, 2002)
The objective of this study was to initially assess the knowledge attitudes and health seeking behaviour in relation to STD/HIV/AIDS among a sample of 15-49 year age group person selected from two Divisional Health Service (DHC) areas in the Matale district. A wide disparity was identified between the knowledge on other-STDs and AIDS among community members. A significant number of them (77 per cent) had heards of other-STDs while 99.4 per cent had heard of AIDS. Among those who had heard of the disease the knowledge on modes of transmission was satisfactory. Knowledge on preventive methods, laboratory services and general awareness on othe-STD was poor. The services offered by PHCWs in relation to the STD prevention at the pre-intervention survey were poor and the knowledge on Other-STDs and their services related practices in realtion to STDs were not satisfactory.This study has demonstrated that both community members and PHCWs do acquire new knowledge and change attitudes and services related practices when exposed to a wellplanned, comprehensive educational intervention and thereby improve the services available for the community.